Acompanhamento clínico e laboratorial de pacientes submetidas à cirurgia combinada de lipoaspiração e abdominoplastia - FERREIRA, Diego Rabelo (2019)
Liposuction and abdominoplasty are well-known aesthetic surgical procedures in the world, so the study of its complications related to preoperative, postoperative and high hemoglobin values are of great importance. The present study was developed in the period from December 2017 to March 2018, at the Spani Vendramin Clinic of Plastic Surgery and Aesthetic Surgery, being outlined in a transverse, prospective and descriptive character. Sixteen patients were evaluated, all being female (100%). The 16 patients evaluated underwent liposuction and abdominoplasty and had, on average, 35 years of age, having a standard deviation of 5.75. The median age was 33 years, being the minimum age of 23 years and the maximum age of 45 years. Sixteen patients underwent liposuction + abdominoplasty (81.25%) and three of them submitted to mammoplasty + liposuction + abdominoplasty in a combined procedure (18.75%). When correlating the hemoglobin fall from the immediate preoperative with medical release and medical release alone with the presence of symptoms in the patients, it was not possible to observe statistical correlation (p-value = 0.2553 and p-value = 0.5022 respectively). When the hemoglobin fall was correlated in the immediate preoperative period and in the immediate postoperative period with the quality of liposuction (p-value = 0.9525), percentage of fluid in the liposuction (p-value = 0.5841), body surface liposuction (p = 0.8531) and percentage of liposuction volume weight (p-value = 0.5841) it was not possible to observe statistical correlation the variables. When correlating the mean hemoglobin fall in the immediate preoperative and the immediate postoperative period with the mean hemoglobin fall in the immediate preoperative period and in the discharge, it was possible to observe statistical significance (p <0.0001). There is no relationship between hemoglobin fall and the presence of symptoms in the postoperative period of patients undergoing liposuction and abdominoplasty, in agreement with the literature while in patients with hemoglobin ≥10mg / dL, and we can consider hemodilution as a participant in this multifactorial event. The quality of the liposuction, the total volume of liposuction, the percentage of liquid in the liposuction and the preoperative weight are not related to the drop in hemoglobin in the patients in this study. However, there is a relationship between the mean decrease in pre / post and pre / medical discharge hemoglobin, being 2.5 mg / dL and 3.8 mg / dL, respectively.